Analisis Pengaruh Keterbukaan Impor Ekspor Terhadap Produk Domestik Regional Bruto (PDRB) DKI Jakarta 2018-2022 - Amanda Putri; Agryani Petra Sitorus; Eka Rindah Yani; Muhammad Tsaqifa Ifada; Maunisa Widya Zalianty; Rahul Abi Ubaidillah; Rasidin Karo Karo Sitepu (Jurnal Ekonomi dan Pembangunan Indonesia, 2024)
The economic development of a region involves examining its Gross Regional Domestic Product (GRDP). The index number method of openness used in this study aims to determine the level of economic openness of a region. This research utilizes secondary data obtained from the Central Bureau of Statistics (BPS) for the period 2018–2022. The research findings indicate that the average export index is 105.0% per-year, indicating an increase in value of exports by 5.0% per-year, the average import index is 87.4% per-year, indicating a decrease in the value of imports by 12.6% per year. Average net export index is 122.9% per-year, indicating an increase in the value of exports by 22.9% per-year. DKI Jakarta demonstrates a strong economic growth rate with an increase in GRDP of 3.1% per-year, as well as showing stable economic activity indicators with an average GRDP index of 103.1% per-year. GDP is directly influenced by exports, an increase in GRDP does not necessarily increase the value of exports. DKI Jakarta has a high economic value, emphasizing the importance of diversifying different types of exports to expand trade networks and enhance competitiveness. The government should reduce dependence on imported goods and increase local production in certain fields..